Development of modified depression anxiety stress scale-depression in determining depression among tyroid disorder patients - Siti Nur Illiani binti Jaafar
Thyroid disorder patients have a high chance of experiencing depression, resulting from multifactorial aspects including biological, psychological and sociological. Eventhough many tools available to screen depression, there was lack of tool to screen depression among thyroid disorder patients. Therefore, the objective of the study was to develop modified depression anxiety stress scale-depression. The cross-sectional study was carried out at four selected government hospitals in Malaysia. The participants included 846 thyroid disorder patients who had follow-ups at the endocrinology clinics in the selected hospitals. Data were collected from 1st March 2016 until 28th February 2017 using three questionnaires, including the Depression Anxiety Stress Scale-Depression (DASS-D), the List of Threatening Experiences (LTE) and the Multidimensional Scale of Perceived Social Support (MSPSS). The findings of this study showed that 13.9% (n = 118/846) had various depression levels, from mild to extremely severe depression; depression was more common among the group of patients with hypothyroidism. Meanwhile, young adult (p = 0.001), high TSH (p = 0.05), stressful life events (p = 0.01) and low perceived social support (p = 0.01) were found to have significant association with depression among thyroid disorder patients. The model of factors associated with depression among thyroid disorder patients was fitted with Modified Depression Anxiety Stress Scale-Depression (MDASS-D) demonstrated good fit in CFA with adequate divergent and convergent validity and good factor loading (0.62-0.83). The MDASS-D also displayed excellent internal consistency with Cronbach's alpha of 0.91. Therefore the MDASS-D is reliable to screen depression among thyroid disorder patients.